The Relation between Omani Students' Perceptions of the Writing Strategies and their Writing Performance - Juma B. Busaidi; Dina A. Al-Jamal (Sultan Qaboos University, 2015)
The present study aimed at exploring the relation between Omani students' percep-tions of writing strategies and their own writing performance. Three types of key universal strategies (metacognitive, cognitive, social-affective), in master's degree research, were assumed as effective in promoting students' successful writing processes. A strategy questionnaire in or-der to map Omani EFL students' perception of strategy use as well as a writing test to identify students' actual writing performance was constructed. The present study reported that the par- ticipants perceived the metacognitive strategy of selective attention as prevailing in their writing practice. They also demonstrated interest in the social affective strategy of cooperation. Cogni-tive strategy use, however, seemed to be complex and challenging, and was perceived as the least apparent. Furthermore, the study reported inefficiency of strategy use, as obtained by the questionnaire, which corresponded with students' very poor performance in the writing test. The test scores indicated that 84.40% of the participants failed the writing test, which means that they are far away from being successful language writers.